Molecular characterization of ulcerative colitis-associated colorectal carcinomas - Hirsch, Daniela; Hardt, Julia; Sauer, Christian; Heselmeyer-Hadded, Kerstin; Witt, Stephanie; Kienle, Peter; Ried-Güldenstubbe, Thomas; Gaiser, Timo (Modern pathology, 2021)
Patients with ulcerative colitis (UC) are at increased risk for developing colorectal cancer (CRC). In contrast to sporadic colorectal tumorigenesis, TP53 mutations occur early in the progression from inﬂamed colonic epithelium to dysplasia to CRC, and are sometimes readily detectable in inﬂamed, (yet) non-dysplastic mucosa. Here, we analyzed formalin-ﬁxed parafﬁn-embedded tissue samples from 19 patients with long-standing UC (median 18 years, range 3 to 34) who had developed CRC as a consequence of chronic inﬂammation of the large bowel. We performed microsatellite instability testing, copy number analysis by array-based comparative genomic hybridization, mutation analysis by targeted next generation sequencing (48-gene panel) and TP53 immunostaining. The results were compared to The Cancer Genome Atlas (TCGA) data on sporadic CRC. All UC-CRC lesions in our cohort were microsatellite stable. Overall, genomic imbalances of UC-CRCs showed patterns of chromosomal aneuploidies characteristic for sporadic CRC with the exception of gains of chromosome arm 5p (12 of 23 UC-CRC, 52%), which are rare in sporadic CRCs from TCGA (21 of 144, 15%; FDR adjusted P = 0.006). UC-CRCs showed a predilection for TP53 alterations, which was the most frequently mutated gene in our cohort (20 of 23, 87%). Interestingly, spatially separated tumor lesions from individual patients tended to harbor distinct TP53 mutations. Similar to CRCs arising in a background of Crohn’s colitis, the genetic landscape of UC-CRCs was characterized by TP53 mutations and chromosomal aneuploidies including gains of chromosome arm 5p. Both alterations harbor the potential for early detection in precursor lesions, thus complementing morphologic diagnosis.
Gesehen am 10.11.2023